RESEARCH ON THE CONSTRUCTION OF CORE CURRICULUM STANDARDS FOR CROSS-BORDER E-COMMERCE MAJORS BASED ON HIGHER VOCATIONAL EDUCATION IN INNER MONGOLIA - Zhao, Rong (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
Taking the cross-border e-commerce major of Inner Mongolia higher vocational education as the research object, this paper analyses the current situation of cross-border e-commerce major curriculum and teaching quality of higher vocational education in Inner Mongolia through the study of domestic and international cross-border e-commerce major curriculum standards, and constructs the core curriculum standard of cross-border e-commerce major of higher vocational education in Inner Mongolia on the basis of this. In addition, the implementation plan of the core curriculum for cross-border e-commerce majors including specific measures such as curriculum setting, teaching methods, and selection of teaching materials is explored, with a view to providing reference value for the teaching reform and talent cultivation of cross-border e-commerce majors in Inner Mongolia's higher vocational education.